Manhaj Ta’lim At-Ta’birat Al-Istilahi Fi Al Arabiyah Al-Mu’ashirah - Hisan Mursalin; Ahmed Al-Khatib; Muhamad Taupik Asegap (Ukazh: Journal of Arabic Studies, 2021)
تهدف هذه الدراسة إلى التعرف على التعبيرات الاصطلاحية من خلال "معجم التعبير الاصطلاحي في العربية المعاصرة للدكتور محمد محمد داود"، وذلك بذكر المعنى اللغوي والاصطلاحي من قبل المؤلف نفسه دون اعتماد على معجم آخر، بحيث إنها تعين الطلابة على إثراء اللغة وترقيتها وبيان كيفية وضع منهج مقترح لتعليم التعبيرات الاصطلاحية لدى طلاب المستوى الرابع قسم تعليم اللغة العربية بجامعة الراية. إن هذه الدراسة تسلك على منهج الوصف التحليلي، وذلك بتتبع التعبيرات الاصطلاحية من خلال "معجم التعبير الاصطلاحي في العربية المعاصرة للدكتور محمد محمد داود (حرف الصاد حتى العين)" وجمعها، وتصنيفها، وعرضها والاستنتاج.كشفت الدراسة وجود التعبيرات الاصطلاحية في "معجم التعبير الاصطلاحي في العربية المعاصرة للدكتور محمد محمد داود (حرف الصاد حتى العين)". وبلغ عدد التعبيرات الاصطلاحية الباحث 247 تعبيرة اصطلاحية. وأيضا من المناهج المقترحة في التعليم، وضعها في تصميم صياغة الحوارات، والأخير وضعها في نصوص فهم المقروء والتدريبات وتعبير موجه. This study aims to identify idiomatic expressions through the "glossary of idiomatic expression in contemporary Arabic by Dr. Muhammad Muhammad Dawud", by mentioning the linguistic and idiomatic meaning by the author himself without relying on another dictionary, so that it helps the ability to enrich the language and its promotion and show how to develop a curriculum A proposal to teach idiomatic expressions for the fourth level students, Arabic language teaching department, Ar-Raayah University. This study follows the analytical description method, by tracking idiomatic expressions through the "Lexicon of Idiomatic Expression in Contemporary Arabic by Dr. Muhammad Muhammad Dawud (Harf Al-Sad to Al-‘Ain)" and collecting, classifying, presenting and concluding it. The study revealed the existence of idiomatic expressions in the glossary of idiomatic expression in contemporary Arabic by Dr. Muhammad Muhammad Dawud (Harf al-Sad to Al-Ain). The number of idiomatic expressions the researcher reached 247 idioms. And also from the proposed curricula in education, put them in designing the formulation of dialogues, and the last put them in the texts of reading comprehension, exercises, and targeted expression.